Diseño de un Centro de Alojamiento para el Hospital SOLCA-Núcleo de Tungurahua, en la parroquia Izamba - Sánchez Villalva, Leslie Astrid (2025)
This graduation project focuses on the architectural design of lodging for cancer patients and their companions. It will be linked to the SOLCA-Núcleo de Tungurahua Hospital, located in the parish of Izamba. This hospital is the only institution in the city of Ambato that offers specialized medical treatment in oncology. The main objective of the architectural proposal is to offer a comprehensive solution that combines functionality, accessibility and humanized design, responding to the needs of its users. The main users will be patients who come from other provinces to be treated at SOLCA Tungurahua and receive chemotherapy treatments, either in a hospital or outpatient setting. These patients also have to attend medical appointments regularly and, in some cases, require adequate spaces for post-surgical rest. On the other hand, the center is not only conceived as a resting space for outpatient users, but is also intended as a meeting and coexistence point between patients. The methodology used includes a qualitative approach, combining an analysis of specialized bibliography with interviews. The results of the research underline the importance of implementing spaces that incorporate the use of color, organic forms and elements that favor the connection with nature. The architectural proposal is developed through an analysis of the needs of the users, of project references and a diagnosis of the implementation site, which allows to establish guidelines on spaces that integrate areas of rest, coexistence and recreation.